Flashover characteristics of bentonite contaminated insulation surfaces under high voltage conditions - Rusli, Halimatusaadiah (2014)
Insulator contamination is a major problem that causes flashover that will make the insulator to deteriorate and age faster than usual. This may jeopardize the security of high voltage systems and lead to damage and economical losses to the client. A number of investigations on insulation contamination have been published and most of them focused on the effects of salt compounds whereas only few of them use other materials as the contaminant. For that reason, this study has been carried out with the view of addressing the influence of bentonite as the main source of artificial pollution contamination on outdoor insulation characteristics in a high voltage system. Bentonite is one example of a good backfill material that was widely used as a conductivity enhancing material for grounding systems. Bentonite was used to provide a low earth resistance in the grounding systems used in lightning protection, power and signal systems. However this compound is easily puffed off during unloading and mixing operations. Therefore as the grounding systems are installed in construction sites, there is a high chance that bentonite dust will be spread with air and settle on nearby insulator surfaces. Such contamination may provide low resistive path for leakage streamers along the insulation surfaces of HV systems that may result surface flashover. Depending on the frequency (number of events per unit time), current amplitude, adherence to the surface and other environmental effects such surface flashover may accelerate degradation of insulation materials. Experiments have been carried out at high voltage laboratories in Universiti Putra Malaysia, Universiti Teknologi Malaysia and Tenaga Nasional Berhad Research to accomplish the objectives. Perspex, polyethylene and rubber insulator have been selected for impulse and alternating voltage testing under clean and bentonite-contaminated surface conditions. The withstand voltage (V50%), voltage at breakdown, time to breakdown (tb) and the behaviour of arcing path of discharge channel were investigated and all the data gathered has been subjected to statistical analysis which includes paired t-test. The outcomes indicate that the presence of bentonite contaminants has changed the insulator characteristics in certain circumstances such as the effects on the voltage at breakdown (under negative polarity), the 50% breakdown voltage (under negative polarity), and the time to breakdown (under wet condition for both negative and positive polarity) and also promote the adherence of arcing path to the insulator surface which could lead to fast surface degradation. Findings of this research may assist power engineers in improving the characteristics of outdoor insulation materials in the future.